SOSIALISASI KELENGKAPAN DAN KETEPATAN PEMERIKSAAN FISIK DAN PENUNJANG MEDIS MEMPENGARUHI KEAKURATAN KODE PNEUMONIA DI RS.BENGKULU - Heltiani, Nofri; Agusianita, Agusianita; Khairunnisyah, Khairunnisyah (APTIRMIKI, 2025)
Ministry of Health of the Republic of Indonesia Number HK.02.02/Menkes/514/2015 states that pneumonia is one of the diseases that often causes medical disputes due to disagreements between BPJSKesehatan and Advanced Health Facilities regarding medical issues that are not in accordance with the Clinical Practice Guidelines. This is due to incompleteness and inaccuracy of the results of physical examinations and medical support (thorax radiographs) recorded in the patient's medical record, so that the process of coding the diagnosis of pneumonia becomes inaccurate. This Community Service Activity aims to provide an overview to casemix officers about the effect of incompleteness and inaccuracy of medical information reviewed from the results of physical examinations and medical support on the accuracy of pneumonia diagnosis codes at Bengkulu Hospital. The method used is socialization and interactive discussion targeting the Head of Casemix and 9 casemix officers. The results of the evaluation through pretest and posttest showed an increase in knowledge and understanding of casemix officers before and after being given socialization by 61% with an average pretest of 56.00 and posttest to 90.00. This activity needs to be carried out as an effort to improve the quality of health services and increase the awareness and understanding of casemix officers regarding the importance of completeness and accuracy of physical examinations and medical support in supporting code accuracy.